Realization of DTMOS based CFTA and multiple input single output biquadratic filter application - Basak, Muhammed Emin (ELSEVIER GMBH, 2019)
Analog filters can be found in everything from mobile phones to disk drives, from audio systems to power supplies, from telecommunications to broadband internet connection. Analog filters can be formed from a variety of active elements. In this study, the Dynamic Threshold Voltage MOSFET (DTMOS) based Current Follower Transconductance Amplifier (CFTA) active element has been suggested and a multi input single output (MISO) universal biquadratic filter has been obtained with this active element. The proposed circuit operates with +/- 0.2 V supply voltages and consumes 140 mu W power and electronically tunable. All five filtering responses have been realized by selecting the different input signals. All simulations have been performed with LTSpice program using the Predictive Technology Model (PTM) 45 nm Level 54 CMOS process parameters. Analysis of AC/DC, noise, Monte Carlo, temperature, total harmonic distortion (THD) proves that the circuit operates in harmony with the theory. With Monte Carlo analysis, it has been observed that the filter achieves stable output against both passive element and process parameter tolerance. It is hoped that the proposed active element and the filter will be useful in ultra-low voltage, low power, and low frequency analog signal applications. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: CFTA; DTMOS; Filter; MISO type; Low voltage; Low power; VOLTAGE MOSFET DTMOS; CURRENT-MODE; AMPLIFIER; Engineering; Telecommunications